Investigation of narrow band random fiber ring laser based on random phase-shift Bragg grating. (August 2019) - Zhang, Ailing; Hao, Liyue; Geng, Bo; Li, Dan
Highlights: A random fiber ring laser based on a 25 mm long random phase-shift grating is experimentally demonstrated. A narrow band single-wavelength random fiber laser with the 3 dB bandwidth of 0.44 pm is realized with a 980 nm laser. The number of emitted wavelengths is changeable by adjusting the pump power. The lasing wavelength near 1549.96 nm presents a maximum fluctuation range of only 1.1 pm over time. The laser can be operated at more stable single-wavelength mode with the random grating exposed to water. Abstract: A random fiber laser based on a 25 mm long random phase-shift fiber Bragg grating with a ring cavity is experimentally demonstrated in this paper. The random phase-shift grating is fabricated with the beam-scanning method in a single-mode fiber. The random feedback and light localization are achieved by introducing 20 phase-shift points with random amplitudes along the grating length. A narrow band single-wavelength random fiber laser with the 3 dB bandwidth of 0.44 pm is realized with a 980 nm laser pumping at 130 mW. The optical signal-to-noise ratio up to 55 dB is obtained at the same pump power. The pump threshold is only 21.8 mW. The number of emitted wavelengths is changeable by adjusting the pump power. The lasing wavelength near 1549.96 nm presents a maximum fluctuation range of only 1.1 pm over time. With the random grating exposed to water, the mode competition is suppressed and the laser can be operated at more stable single-wavelength mode.